Examining the Potential Gender Gap in Online Health Information-Seeking Behaviors Among Digital Natives. Issue 4 (1st October 2016) - McGloin, Rory; Richards, Keith; Embacher, Kimberly
Abstract : This investigation focused on gender differences in young adults related to health consciousness and online health information seeking. Contrary to prior research, gender was not a significant predictor of either health consciousness or health information-seeking behavior. Furthermore, health consciousness was found to be a more influential predictor of online health information-seeking behaviors than gender.